2014
DOI: 10.1007/s12076-014-0124-0
|View full text |Cite
|
Sign up to set email alerts
|

HOW TO GO GREEN: a general equilibrium investigation of environmental policies for sustained growth with an application to Turkey’s economy

Abstract: Green growth is a relatively new concept aimed at focusing attention on achieving sustainable development through the efficient use of environmental assets without slowing economic growth. This paper presents a real-world application of the concept, and identifies viable policy options for achieving a complementary environmental regulatory framework that minimizes output and employment losses. The analysis utilizes macro level data from the Turkish economy, and develops an applied general equilibrium model to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
0
9
0
3
Order By: Relevance
“…The model is composed of 12 production sectors spanned over two regionalization bodies for the Turkish economy as High versus Low Income; a representative private household to carry out savings-consumption decisions; a government to implement public policies towards environmental abatement; and a "rest of the world" account to resolve balance of payments transactions. Antecedents of the model rest on the seminal contributions of the CGE analyses on gaseous pollutants, energy utilization, and economics of climate change for Turkey as narrated in Lise (2006), Kumbaroglu (2003), Sahin (2004), Vural (2009), and Telli et al (2008), Akin-Olcum and Yeldan (2013) Voyvoda and Yeldan (2011) and Bouzaher et al (2015). All these, however, were based on national aggregates.…”
Section: Methodology: the Analytical Modelmentioning
confidence: 99%
“…The model is composed of 12 production sectors spanned over two regionalization bodies for the Turkish economy as High versus Low Income; a representative private household to carry out savings-consumption decisions; a government to implement public policies towards environmental abatement; and a "rest of the world" account to resolve balance of payments transactions. Antecedents of the model rest on the seminal contributions of the CGE analyses on gaseous pollutants, energy utilization, and economics of climate change for Turkey as narrated in Lise (2006), Kumbaroglu (2003), Sahin (2004), Vural (2009), and Telli et al (2008), Akin-Olcum and Yeldan (2013) Voyvoda and Yeldan (2011) and Bouzaher et al (2015). All these, however, were based on national aggregates.…”
Section: Methodology: the Analytical Modelmentioning
confidence: 99%
“…A more in-depth discussion and modelling of skills requirements can be found in the green growth literature (e.g. (OECD/Cedefop, 2014 [65]; ILO, 2011 [66]; Botta, 2018 [67])). Some circular economy job categories, such as recycling and waste are mentioned alongside other green job categories in some of these studies (Cedefop, 2010[68]).…”
Section: Skills Requirements For a Resource Efficient And Circular Ecmentioning
confidence: 99%
“…The authors built a multi-regional, multi-sectoral applied general equilibrium model, and found that Turkey would have economic gains from linking with the EU ETS under the 20% cap, but it would suffer critical output loss under the 30% cutback. Bouzaher, Sahin and Yeldan [43] built a 12-sector, dynamic CGE model which included CO 2 and Particulate Matter (PM10) emissions, solid waste and waste water discharges. The authors aimed to identify viable policies for the 2010-2030 period to realize green growth in Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%